Long-Lasting Rituximab-Induced Reduction of Specific—But Not Total—IgG4 in MuSK-Positive Myasthenia Gravis - Marino, Mariapaola; Basile, Umberto; Spagni, Gregorio; Napodano, Cecilia; Iorio, Raffaele; Gulli, Francesca; Todi, Laura; Provenzano, Carlo; Bartoccioni, Emanuela; Evoli, Amelia (Frontiers in Immunology, 2020)
The use of rituximab (RTX), an anti-CD20 monoclonal antibody (Ab), in refractory myasthenia gravis (MG) is associated with a better response in patients with Abs to the muscle-specific tyrosine kinase (MuSK) than in other MG subgroups. Anti-MuSK Abs are mostly IgG4 with proven pathogenicity and positive correlation with clinical severity. The rapid and sustained response to RTX may be related to MuSK Ab production by short-lived Ab-secreting cells derived from specific CD20+ B cells. Here, we investigated the long-term effects of RTX in nine refractory MuSK-MG patients with a follow-up ranging from 17 months to 13 years. In patients’ sera, we titrated MuSK-specific IgG (MuSK-IgG) and MuSK-IgG4, along with total IgG and IgG4 levels. Optimal response to RTX was defined as the achievement and maintenance of the status of minimal manifestations (MM)-or-better together with a ≥ 50% steroid reduction, withdrawal of immunosuppressants, and no need for plasma-exchange or intravenous immunoglobulin. After a course of RTX, eight patients improved, with optimal response in six, while only one patient did not respond. At baseline, MuSK-IgG and MuSK-IgG4 serum titers were positive in all patients, ranging from 2.15 to 49.5 nmol/L and from 0.33 to 46.2 nmol/L, respectively. MuSK Abs mostly consisted of IgG4 (range 63.80–98.86%). RTX administration was followed by a marked reduction of MuSK Abs at 2–7 months and at 12–30 months (p < 0.02 for MuSK-IgG and p < 0.01 for MuSK-IgG4). In patients with a longer follow-up, MuSK Ab titers remained suppressed, paralleling clinical response. In the patient who achieved long-term complete remission, MuSK-IgG4 was no longer detectable within 2 years, while MuSK-IgG remained positive at very low titers up to 10 years after RTX. In the patient who did not respond, MuSK-IgG and MuSK-IgG4 remained unchanged. In this patient series, total IgG and IgG4 transiently decreased (p < 0.05) at 2–7 months after RTX. The different trends of reduction between MuSK-IgG4 and total IgG4 after RTX support the view that short-lived Ab-secreting cells are the main producers of MuSK Abs. The ratio between short-lived Ab-secreting cells and long-lived plasma cells may influence the response to RTX, and B-cell severe depletion may reduce self-maintaining autoimmune reactivity.